Palliative intubation of oesophagogastric neoplasms at fibreoptic endoscopy. Issue 12 (December 1982) - Ogilvie, A L; Dronfield, M W; Ferguson, R; Atkinson, M
Abstract : Of one hundred and twenty-one patients with neoplastic obstruction of the oesophagus or cardia 118 underwent palliative intubation at fibreoptic endoscopy on a total of 135 occasions. Sixty had adenocarcinoma, 49 had squamous carcinoma, and in nine the oesophagus was involved by a growth arising elsewhere. Satisfactory swallowing ws restored in 112 patients. Thirteen patients died in hospital shortly after the procedure. Five fatal and 10 non-fatal perforations were sustained in 135 intubation procedures. Complications of tube function included food blockage on 26 occasions, tumour overgrowth on seven occasions, displacement on 16 occasions, disappearance of the tube in two patients, and late oesophageal perforation on nine occasions. Fifty-six patients survived for three months, 33 for six months, and 10 for a year after intubation. Comparison with series in the literature of patients who underwent surgical palliative intubation suggests that endoscopic palliation has lower mortality and morbidity, and an increased survival time, and is now the method of choice for palliation of oesophagogastric neoplasms.